Probabilistic seismic collapse risk assessment of non-engineered masonry buildings in Malawi - Goda, Katsuichiro; Williams, Jack; De Risi, Raffaele; Ngoma, Ignasio (Frontiers in Built Environment, 2024)
This study presents the most recent development of a nationwide earthquake risk model for nonengineered masonry buildings in Malawi. Due to its location within the East African Rift, Malawi experienced several moderate earthquakes that caused seismic damage and loss. Recently, a new probabilistic seismic hazard model has been developed by considering fault-based seismic sources, in addition to conventional areal sources. The most recent 2018 national census data provide accurate exposure information for Malawian people and their assets at detailed spatial resolutions. To develop seismic fragility functions that are applicable to Malawian housing stocks, building surveys and experimental tests of local construction materials have been conducted. By integrating these new developments of seismic hazard, exposure, and vulnerability modules, a quantitative seismic building collapse risk model for Malawi is developed on a national scale. For the rapid computation of seismic risk curves at individual locations, an efficient statistical approach for approximating the upper tail distribution of a seismic hazard curve is implemented. Using this technique, a seismic risk curve for a single location can be obtained in a few seconds, thereby, this can be easily expanded to the whole country with reasonable computational times. The results from this new quantitative assessment tool for seismic impact will provide a sound basis for risk-based disaster mitigation policies in Malawi.* ln is the natural logarithm, P is the cumulative probability, and  -1 (•) is the inverse standard normal distribution function; ** N(0,1) is a standard normal random number and U(0,1) is a standard uniform random number.